2015
DOI: 10.1111/php.12480
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Photoactive Dye Methylene Blue versus Caspofungin on the Candida parapsilosis Biofilm in vitro and ex vivo

Abstract: This research studied the effectiveness of the photoactive compound methylene blue (MB) activated with red LED light (576-672 nm) compared to that of caspofungin (CAS) on 1 Candida albicans and 3 Candida parapsilosis strains. Results were evaluated in terms of SMIC50 for CAS or in PDI (photodynamic inactivation)-SMIC50 for MB (minimal inhibitory concentration inhibiting sessile biofilm to 50% in comparison to the control without CAS or after irradiation in comparison to the control without MB). While all strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The comparison with our data and the possible explanation is very difficult because the methodology used is dissimilar [ 31 ]. Černáková et al demonstrated that using 9.6 μg/mL of MB inhibited between 1.13–1.27 log 10 of C. parapsilosis in suspension, similar results to this work (this concentration does not generate complete photoinactivation) [ 32 ]. Finally, Ahmed et al used 100 μg/mL of MB and achieved reductions of 0.58–0.85 log 10 at fluences of 90–180 J/cm 2 respectively [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…The comparison with our data and the possible explanation is very difficult because the methodology used is dissimilar [ 31 ]. Černáková et al demonstrated that using 9.6 μg/mL of MB inhibited between 1.13–1.27 log 10 of C. parapsilosis in suspension, similar results to this work (this concentration does not generate complete photoinactivation) [ 32 ]. Finally, Ahmed et al used 100 μg/mL of MB and achieved reductions of 0.58–0.85 log 10 at fluences of 90–180 J/cm 2 respectively [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…The photosensitizer toluidine blue (0.1 mg/mL) has been used successfully, reducing up to 60% the formation of C. albicans biofilms ( 152 ). Another promising photosensitizer is methylene blue, capable of preventing C. parapsilosis biofilm formation ex vivo on mouse tongues after being activated by red LED light ( 153 ). Interestingly, the combination of photodynamic inactivation strategy, using toluidine blue, together with chitosan, results in an enhancement of the effect of both approaches against Candida biofilms ( 154 ).…”
Section: Promising Strategiesmentioning
confidence: 99%
“…The oral cavity provides an optimal environment for biofilm formation (Zaura et al, 2009 ). Up to now, three types of PS, erythrosine (Costa et al, 2012a ), MB (Cernáková et al, 2015 ), and Photogem (Mima et al, 2010 ) have been employed to suppress oral biofilms in animal models.…”
Section: Preclinical In Vivo Animal Studies Using mentioning
confidence: 99%
“…Topical application of MB and laser irradiation using a diffusing fiber reduced C. albicans by 2.74 log 10 steps in an immunosuppressed murine model (Teichert et al, 2002 ). Recently, Cernáková et al also reported that photoactivated MB could totally eradicate biofilms of C. parapsilosis formed on the tongue of BALB/c female mice (Cernáková et al, 2015 ).…”
Section: Preclinical In Vivo Animal Studies Using mentioning
confidence: 99%